Fatty alcohol oxidase 3 (FAO3) and FAO4b connect the alcohol- and alkane-forming pathways in Arabidopsis stem wax biosynthesis. (5th December 2021) - Yang, Xianpeng; Cui, Lili; Li, Shipeng; Ma, Changle; Kosma, Dylan K; Zhao, Huayan; Lü, Shiyou
Abstract: The alcohol- and alkane-forming pathways in cuticular wax biosynthesis are well characterized in Arabidopsis. However, potential interactions between the two pathways remain unclear. Here, we reveal that mutation of CER4, the key gene in the alcohol-forming pathway, also led to a deficiency in the alkane-forming pathway in distal stems. To trace the connection between the two pathways, we characterized two homologs of fatty alcohol oxidase (FAO), FAO3 and FAO4b, which were highly expressed in distal stems and localized to the endoplasmic reticulum. The amounts of waxes from the alkane-forming pathway were significantly decreased in stems of fao4b and much lower in fao3 fao4b plants, indicative of an overlapping function for the two proteins in wax synthesis. Additionally, overexpression of FAO3 and FAO4b in Arabidopsis resulted in a dramatic reduction of primary alcohols and significant increases of aldehydes and related waxes. Moreover, expressing FAO3 or FAO4b led to significantly decreased amounts of C18 –C26 alcohols in yeast co-expressing CER4 and FAR1 . Collectively, these findings demonstrate that FAO3 and FAO4b are functionally redundant in suppressing accumulation of primary alcohols and contributing to aldehyde production, which provides a missing and long-sought-after link between these two pathways in wax biosynthesis. Abstract : FAO3 and FAO4b suppress accumulation of primary alcohols and contribute to aldehyde production, which connects the alcohol- and alkane-forming pathways in Arabidopsis stem wax biosynthesis.